1989
DOI: 10.1083/jcb.109.1.441
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta activity is potentiated by heparin via dissociation of the transforming growth factor-beta/alpha 2-macroglobulin inactive complex.

Abstract: The control of smooth muscle cell (SMC) proliferation is determined by the combined actions of mitogens, such as platelet-derived growth factor, and the opposing action of growth inhibitory agents, such as heparin and transforming growth factor-beta (TGF-beta). The present studies identify an interaction between heparin and TGF-beta in which heparin potentiates the biological action of TGF-beta. Using a neutralizing antibody to TGF-beta, we observed that the short term antiproliferative effect of heparin depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(103 citation statements)
references
References 61 publications
5
97
0
1
Order By: Relevance
“…by preventing the formation of inactive complexes with a2-macroglobulin (15,16). We found that silencing of enzymes that attach sulfate groups to C-6 of glucosamine residues, HS6ST1 and HS6ST2, inhibited TGF-b induction of IL-11.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…by preventing the formation of inactive complexes with a2-macroglobulin (15,16). We found that silencing of enzymes that attach sulfate groups to C-6 of glucosamine residues, HS6ST1 and HS6ST2, inhibited TGF-b induction of IL-11.…”
Section: Discussionmentioning
confidence: 83%
“…It has been shown that TGF-b1 binds to heparin and highly sulfated liver heparan sulfate, and this potentiates the biologic activity of TGF-b1 (15)(16)(17). It is also well established that heparan sulfate-protein interactions critically depend on the amount and the positions of the sulfate groups (18).…”
Section: Heparin and A Hlgag K5-nsos Inhibit Tgfb-induced Il-11 Produmentioning
confidence: 99%
“…A role of this cell type in the catabolism of bloodborne TGF-␤ has been proposed previously, 52,53 but it is presently not known whether this cytokine circulates in the blood as a component of the large, latent complex, or only bound to ␣ 2 -macroglobulin. [54][55][56] PC, however, could also be relevant for the sequestration of locally produced TGF-␤ complex. Impairment of this mechanism under disease conditions might enhance the half-life time of TGF-␤ (complex) at the site of injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, alpha2-macroglobulin (a2-M) has been found to associate with nerve growth factor (NGF) (Ronne et al, 1979), EGF (Ito et al, 1984), PDGF (Huang et al, 1984) (Borth and Luger, 1989), bFGF (Dennis et al, 1989), IL-6 (Matsuda et al, 1989), and TNF (Wollenberg et al, 1991). Proposed functions for a2-M in regulating growth factor activity include clearance of growth factor from the circulation (LaMarre et al, 1991), inhibition or stimulation of activity (Bonner et al, 1990;Shi et al, 1990), protection from proteolytic degradation (Ronne et al, 1979), and delivery of growth factor to distant sites (McCaffrey et al, 1989).…”
Section: Regulation In Time and Spacementioning
confidence: 99%